PERBEDAAN KADAR ZINC SERUM PENDERITA PREEKLAMPSIA BERAT DENGAN KEHAMILAN NORMAL - Ermawati, Ermawati; Bachtiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2018)
Preeclampsia is a major obstruction complication with increasing incidence and is associated with maternal morbidity and mortality. One theory regarding preeclampsia is the development of oxidative stress due to the benefits of pro-oxidant and anti-oxidant functions that consequently results in free radicals, active oxygen, or reactive nitrogen. The deacrease of Zinc as a cofactor of anti-oxidant enzymes is reported to be associated with an increased risk of preeclampsia. Cross sectional comparative study was conducted in Dr. M. DjamilPadangHospital, SolokDistrict Hospital, PainanDistrict Hospital, BatusangkarDistrict Hospital, and Biomedicallaboratoryof Medical Faculty of Andalas University from September 2014 to February 2015. There were 40 samples with pregnancy beyond 20 weeks which were then divided into two groups; severe preeclampsia and normal pregnancy. Serum zinc wasexamined in both groups. Serum zinc in severe preeclampsia and normal pre-stressed demonstrated a significant difference (p <0.05). The mean concentration of serum zinc in severe preeclampsia and in normal pregnancy were 0.45 Â± 0.09 Î¼g / ml and 0.78 Â± 0.55 Î¼g / ml with p = 0.02. This difference is statistically significant with p <0.005. There was a significant difference between serum zinc concentration in normal pregnant women and that in severe preeclamptic women.Keywords: severe preeclampsia, normal pregnancy, zinc serum